The Tudor Staphylococcal Nuclease Protein of Entamoeba histolytica Participates in Transcription Regulation and Stress Response - Cázares-Apátiga, Javier; Medina-Gómez, Christian; Chávez-Munguía, Bibiana; Calixto-Gálvez, Mercedes; Orozco, Esther; Vázquez-Calzada, Carlos; Martínez-Higuera, Aarón; Rodríguez, Mario A. (Frontiers in Cellular and Infection Microbiology, 2017)
Entamoeba histolytica is the protozoa parasite responsible of human amoebiasis, disease that causes from 40,000 to 100,000 deaths annually worldwide. However, few are known about the expression regulation of molecules involved in its pathogenicity. Transcription of some virulence-related genes is positively controlled by the cis-regulatory element named URE1. Previously we identified the transcription factor that binds to URE1, which displayed a nuclear and cytoplasmic localization. This protein belongs to the Tudor Staphyococcal nuclease (TSN) family, which in other systems participates in virtually all pathways of gene expression, suggesting that this amoebic transcription factor (EhTSN; former EhURE1BP) could also play multiple functions in E. histolytica. The aim of this study was to identify the possible cellular events where EhTSN is involved. Here, we found that EhTSN in nucleus is located in euchromatin and close to, but not into, heterochromatin. We also showed the association of EhTSN with proteins involved in transcription and that the knockdown of EhTSN provokes a diminishing in the mRNA level of the EhRabB gene, which in its promoter region contains the URE1 motive, confirming that EhTSN participates in transcription regulation. In cytoplasm, this protein was found linked to the membrane of small vesicles and to plasma membrane. Through pull-down assays and mass spectrometry we identity thirty two candidate proteins to interact with EhTSN. These proteins participate in transcription, metabolism, signaling, and stress response, among other cellular processes. Interaction of EhTSN with some candidate proteins involved in metabolism, and signaling was validated by co-immunoprecipitation or co-localization. Finally we showed the co-localization of EhTSN and HSP70 in putative stress granules during heat shock and that the knockdown of EhTSN increases the cell death during heat shock treatment, reinforcing the hypothesis that EhTSN has a role during stress response. All data support the proposal that EhTSN is a multifunctional protein of E. histolytica.